Socialization of Educational Prevention of Demensional Diseases in The Elderly at The Karang Anyar Health Center, Sidodadi Ramunia Lubuk Pakam Village 2024 - Kesumawardani, Nadya Ulfa; Karokaro, Tati Murni; Syatria Wati; Alfrisa, Bagus; Hayati, Kardina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Dementia is a syndrome of cognitive decline in which the repetitive processing of information from long-term memory occurs. When individuals reach the age of 60 years and over they are categorized as elderly, one of the many problems in the elderly that often arises is dementia/memory decline which will then have a negative impact on cognitive function. Community service is key in efforts to spread knowledge about dementia. This Community Service was carried out for the elderly at the Karang Anyar Community Health Center, Sidodadi Ramunia Lubuk Pakam Village, as many as 50 people. This activity will play a role in raising awareness of the elderly about the need to know knowledge about treating dementia by doing brain exercises that are practiced at the Karang Anyar Community Health Center. This activity is held through counseling and public campaigns, where PkM will be able to increase understanding of the benefits of doing brain exercises for the elderly. Evaluation of this activity is carried out through a review activity by asking the elderly questions regarding the meaning, signs and symptoms as well as treatment for dementia patients. The results of this PkM show that there has been a significant increase in knowledge and efforts to treat dementia at the Karang Anyar Community Health Center in Sidodadi Ramunia Village, Lubuk Pakam.